Upaya Pencegahan dan Perlindungan Hukum terhadap Anak yang Menjadi Korban Perundungan (Bullying) di Lingkungan Sekolah Dasar dan Sekolah Menengah Pertama di Kota Palangka Raya - Andika Haring Putera; Dedi Dedi; Denni Nanda Eka Saputra; Delly Rianto; Joanita Jalianery; Evi Evi (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Bullying in school environments is a serious issue that negatively affects children’s physical, psychological, and social development. As individuals in a growth phase, children have the right to receive adequate legal protection. This study aims to raise students' awareness of the dangers of bullying and to provide an understanding of the available legal protection for victims. The activities were conducted through direct outreach in seven elementary and junior high schools in Palangka Raya using educational videos, banners, and pocket books. The results showed high enthusiasm from students and improved understanding of types of bullying, its impact, and the legal protections available. Collaboration between educational institutions, the government, and society proved effective in creating a safe and child-friendly school environment.